Assessing microvascular dysfunction and predicting long-term prognosis in patients with cardiac amyloidosis by cardiovascular magnetic resonance quantitative stress perfusion - Leting Tang; Wenjin Zhao; Kang Li; Lin Tian; Xiaoyue Zhou; Hu Guo; Mu Zeng (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Cardiac involvement in light chain amyloidosis (AL) is the main determinant of prognosis. Amyloid can be deposited in the extracellular space and cause an increase in extracellular volume fraction (ECV). At the same time, amyloid can also be deposited in the wall of small vessels and cause microvascular dysfunction. This study sought to investigate the extent of microvascular dysfunction and its incremental prognostic value in cardiac light-chain amyloidosis (AL-CA) by quantitative stress perfusion. Methods: A total of 126 AL amyloidosis patients (61.13 ± 8.46 years, 81 male) confirmed by pathology were prospectively recruited. All subjects underwent cardiovascular magnetic resonance (CMR) with late gadolinium enhancement (LGE), T1 mapping, and stress perfusion on a 3T scanner. ECV and myocardial perfusion reserve (MPR) were measured semi-automatically using a dedicated CMR software. Clinical, laboratory, and CMR parameters were analyzed for their prognostic value in the assessment of AL-CA patients. Mortality-associated markers were analyzed by univariate and multivariable Cox regression. Results: The median follow-up time was 37 (33.6–40.4) months, and 62 patients died. The ECV of survivors was significantly reduced, but the stress myocardial blood flow and MPR were higher (P < 0.001). The MPR of the transmural LGE group was significantly lower than that of the no LGE and subendocardial LGE groups (P < 0.001). In multivariable analysis, ECV, MPR, and LGE were independently predictive. MPR of >1.5 and ECV of ≤53.6% were associated with improved overall survival, both of which provided predictive incremental value in patients with advanced disease. With equal Mayo staging and degree of ECV, MPR improves assessment of patient survival. Conclusion: ECV and MPR showed additive incremental values and further discriminated prognosis of patients in advanced stages. CMR phenotypes with higher ECV and lower MPR had a worse prognosis.